The social imperative : architecture and the city in China - Wee, H. Koon; AA Asia (New York : Actar Publishers, 2017)
This book contains multiple short critiques, reflections and manifestos, affording each contributing architect and intellectual the time and space to imagine new social paradigms in China. Emerging from a tumultuous history of high culture and complex territorial conditions, there is nothing straightforward about the social development of China. The complexity of the social practices developed by architects and shapers of the built environment can be explained in part by the last three decades of an intensified adoption of the market economy by the Communist Party of China, after an equally short three decades of closed-door communist control. There is no political meltdown like the democratization of the former Communist Bloc, but there is a constant managing of discontent and resistance across China. At the apex of the many creative and intellectual forces in China, architects harbor and give form to many tactics of resistance. Unfortunately, architects are also the instruments and minds complicit with profit-mongering developers and governments, pursuing unchecked urbanization, degradation of the environment, exploitation of the marginalized, and the creation of a very inequitable China.
Includes bibliographical references and index.
Keywords: Architecture and society -- China -- History -- 21st century; Architecture and state -- China -- History -- 21st century; Urbanization -- China; Cities and towns -- China -- Growth; Architectural design; Architecture and state; City planning; China -- Social conditions -- 2000-; China